Analysis of Open Website Security Using OWASP and ISSAF Methods - Rahmad Ashar (Jurnal Informasi dan Teknologi, 2022)
Diskominfo Kerinci is an agency responsible for the management of information media within the Kerinci Regency Government. The existence of a website as a medium of information is a very important need to convey information to the public. This managed website is public (open website) so that information security principles must be applied so as not to get cyber attacks. This study conducted a security analysis on an open website owned by Diskominfo Kerinci using two methods, namely the Open Web Application Security Project (OWASP) method and the Information Systems Security Assessment Framework (ISSAF) method. Research related to the use of the OWASP and ISSAF methods in system security testing has been carried out, several tests state that this method greatly influences the steps and results of system security testing. The results of the security analysis from these two methods will be compared to make recommendations for improvements to the website.